2009
DOI: 10.1086/605436
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Rapid Diagnostic Tests versus Blood Smears for Malaria in US Clinical Practice

Abstract: Background Approximately 4 million U.S. travelers to developing countries are ill enough to seek healthcare with 1,500 malaria cases reported in the U.S. annually. The diagnosis of malaria is frequently delayed due to the time to prepare malaria blood films and lack of technical expertise. An easy, reliable rapid diagnostic test (RDT) with high sensitivity and negative predictive value (NPV), particularly for Plasmodium falciparum, would be clinically useful. The study objective was to determine the diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 19 publications
2
65
2
2
Order By: Relevance
“…BinaxNOW is known to have a lower sensitivity for P. ovale at lower parasitemia (5, 9). The current findings are similar to previous reports from the United States, Canada, and France, with 94 to 97% sensitivity for P. falciparum and 67 to 86% sensitivity for non-falciparum malaria using BinaxNOW (4,5,17). As would be expected with qualitative antigen testing, low parasitemia can cause false-negative results, as observed here and in other studies, including one from Canada that showed 75% sensitivity for P. falciparum at a parasitemia of 1 to 100/l (Ͻ0.002%), and 96.2% sensitivity at 101 to 1,000/l (Ͻ0.02%) (5).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…BinaxNOW is known to have a lower sensitivity for P. ovale at lower parasitemia (5, 9). The current findings are similar to previous reports from the United States, Canada, and France, with 94 to 97% sensitivity for P. falciparum and 67 to 86% sensitivity for non-falciparum malaria using BinaxNOW (4,5,17). As would be expected with qualitative antigen testing, low parasitemia can cause false-negative results, as observed here and in other studies, including one from Canada that showed 75% sensitivity for P. falciparum at a parasitemia of 1 to 100/l (Ͻ0.002%), and 96.2% sensitivity at 101 to 1,000/l (Ͻ0.02%) (5).…”
Section: Discussionsupporting
confidence: 91%
“…Studies in France have demonstrated 96% sensitivity, 99% specificity, and high negative predictive values (NPV) with certain RDTs but conclude that microscopy is necessary for definitive confirmation (3,4). A similar study in the United States demonstrated 99% overall sensitivity and 99.6% NPV for the diagnosis of malaria with the BinaxNOW Malaria test; sensitivity for P. falciparum was 100% (17). BinaxNOW Malaria, the only U.S. Food and Drug Administration-approved RDT for malaria, qualitatively detects both the histidine-rich protein 2 (HRP-2), specific to P. falciparum, and aldolase, a panmalarial antigen found in all Plasmodium species (11).…”
Section: T He Accurate Diagnosis Of Malaria By Microscopy In the Unitedmentioning
confidence: 99%
“…1,2 Rapid diagnostic tests for malarial antigens can sometimes outperform blood smears in developed world settings, 3 but they are less specific in regions of high prevalence and following drug treatment. 4 A variety of molecular methods of malaria parasite detection were developed in the past 20 years and include singlestep and nested polymerase chain reaction (PCR) with gel detection, RNA-specific nucleic acid-based sequence amplification (NASBA), and probe-based real-time PCR and reverse transcription (RT)-PCR (using various combinations of genus-or species-specific primers and TaqMan probes or molecular beacons).…”
Section: Introductionmentioning
confidence: 99%
“…A recent report found that Binax NOW RDT had a negative predictive value of 100% for P. falciparum malaria and 98% for all malaria in a U.S. clinical laboratory setting. 9 Despite the excellent capacity of RDTs to exclude malaria, serial testing is generally still recommended. 2 However, fewer tests could dramatically improve patient waiting times, laboratory and hospital efficiency, and costs.…”
Section: Introductionmentioning
confidence: 99%